ANALISIS PERBEDAAN PERSEPSI KONSUMEN MINIMARKET MODERN DAN TOKO KELONTONG DI DESA KARTONATAN, KARTASURA, SUKOHARJO (Studi pada Alfamart dan Toko Kelontong) - Sri Lestari; Burhanudin Ahmad Yani; Ida Aryati DPW (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to determine whether or not there were differing perceptions of consumers of modern minimarkets (Alfamart) and grocery stores based on price, service,product and location. This research is quantitative research, comparative method by drawing conclusions through statistical analysis. The population in this study are consumers who shop at grocery and Alfamart stores. Samples were taken as manyas 100 respondents. Data needed through documents and questionnaires. The questionnaire was test edusingvalidityandreliability.Thedataanalysistechniqueusedwasmulticollinearitytest,heteroscedastitytest,normalitytest,autocorrelationtest. The results of this study show that: 1) Price (X1) there is a significant differencebetween Alfamart and the grocery store Test t -0.755